2020
DOI: 10.1136/bmjopen-2019-035183
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of staffing needs for physicians and nurses at Upazila health complexes in Bangladesh using WHO workload indicators of staffing need (WISN) method

Abstract: ObjectiveThis study aimed to assess the current workload and staffing need of physicians and nurses for delivering optimum healthcare services at the Upazila Health Complexes (UpHCs) in Bangladesh.DesignMixed-methods, combining qualitative (eg, document reviews, key informant interviews, in-depth interviews, observations) and quantitative methods (time-motion survey).SettingStudy was conducted in 24 health facilities of Bangladesh. However, UpHCs being the nucleus of primary healthcare in Bangladesh, this manu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 19 publications
(21 reference statements)
2
29
1
4
Order By: Relevance
“…For example, nurses have had little say over the decisions related to their profession, they were not allowed to perform unsupervised clinical duties, experience heavy workloads leading to performance failures, and a lack of clear plan for career progression. These issues have been supported by other studies as well (Darkwa et al., 2015; Joarder et al., 2020; Zaman, 2009). The dominance of physicians in health sector decision-making and nurses’ disapproval to this, particularly in clinical decision-making is well-documented in other countries as well (Amsalu et al., 2014; Mehrabi et al., 2016).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…For example, nurses have had little say over the decisions related to their profession, they were not allowed to perform unsupervised clinical duties, experience heavy workloads leading to performance failures, and a lack of clear plan for career progression. These issues have been supported by other studies as well (Darkwa et al., 2015; Joarder et al., 2020; Zaman, 2009). The dominance of physicians in health sector decision-making and nurses’ disapproval to this, particularly in clinical decision-making is well-documented in other countries as well (Amsalu et al., 2014; Mehrabi et al., 2016).…”
Section: Discussionsupporting
confidence: 79%
“…The dominance of physicians in health sector decision-making and nurses' disapproval to this, particularly in clinical decision-making is well-documented in other countries as well (Amsalu et al, 2014;Mehrabi et al, 2016). Joarder et al (2020), based on Workload Indicator of Staffing Needs studies, showed that nurses in Bangladesh suffered a high workload (workload indicator of staffing needs ratio of 0.69, where lower than 1 indicates higher workload), and Darkwa et al (2015) showed that lack of career development was a hindrance for nurses to work in rural areas.…”
Section: Discussionmentioning
confidence: 99%
“…It is evident that high workload pressures prevail for physicians and nurses at the UpHCs. This reveals high demand for these health workforces in the respective sub-districts (16). The study was conducted by Farahi Shahgholi aimed to calculation of workload and estimation of the required number of health staff related to family medicine program in East Azerbaijan province based on WISN.…”
Section: Discussionmentioning
confidence: 99%
“…If only the vacant posts are filled, the workload is reduced. In fact, sanctioned number of physicians and nurses is more than actual need (16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation